2022
DOI: 10.1002/uog.26036
|View full text |Cite
|
Sign up to set email alerts
|

Competing‐risks model for pre‐eclampsia and adverse pregnancy outcomes

Abstract: What are the novel findings of this work?Women at 35-37 weeks' gestation that are identified by the competing-risks model to be at high risk of pre-eclampsia are also at increased risk of developing gestational hypertension, Cesarean section, stillbirth, delivering a small-for-gestational-age neonate and having a neonate requiring admission to the neonatal unit for ≥ 48 h. What are the clinical implications of this work?Women identified by third-trimester screening as being at high risk for pre-eclampsia shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several studies 29 have shown that patients with pre-eclampsia have a higher incidence of SGA and FGR. Panaitescu et al showed that the incidence of SGA below the tenth percentile was 28.9% and 11.1% in women with and without pre-eclampsia, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 29 have shown that patients with pre-eclampsia have a higher incidence of SGA and FGR. Panaitescu et al showed that the incidence of SGA below the tenth percentile was 28.9% and 11.1% in women with and without pre-eclampsia, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies 29 have shown that patients with preeclampsia have a higher incidence of SGA and FGR.…”
Section: Discussionmentioning
confidence: 99%
“…The small proportion of MCDA twins scanned at 36 weeks reflects the higher frequency of births occurring before 36 weeks in this group. For comparison, data were available on 29 035 singletons 11 . The median maternal age in DC twins was higher than that in singletons and MCDA twins, reflecting the relatively high proportion of pregnancies conceived by in-vitro fertilization in the DC twin population.…”
Section: Methodsmentioning
confidence: 99%
“…Data on singletons were obtained from a prospective non-interventional observational study of women with a singleton pregnancy attending for a routine hospital visit at 35 + 0 to 36 + 6 weeks' gestation at King's College Hospital, London, and Medway Maritime Hospital, Gillingham, UK, between October 2016 and September 2021 11 .…”
Section: Study Populationmentioning
confidence: 99%
“…Its offspring are prone to premature delivery, fetal distress, fetal growth restriction (FGR), neonatal hypoglycemia, and even death ( Govender et al, 2023 ). The etiology of preeclampsia is multifactorial, including maternal factors such as family history of preeclampsia, multiple pregnancies, chronic kidney disease, and obesity, and placental factors such as uteroplacental insufficiency and increased placental volume/mass ratio ( Syngelaki et al, 2022 ). However, the pathogenesis of preeclampsia has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%